Інформаційно-аналітична підтримка маркетингу: сучасні тренди та виклики - Грінберг, Галина Леонідівна; Конохова, Зоя Петрівна (ТОВ "ДКС Центр", 2025)
Система інформаційно-аналітичної підтримки маркетингової діяльності відіграє ключову роль у сучасному бізнесі, забезпечуючи ефективний збір, обробку та аналіз маркетингової інформації. У статті розглянуто концепцію маркетингової інформаційної системи (МІС), її еволюцію, функціональні можливості та вплив цифрових технологій на розвиток маркетингової аналітики. Особливу увагу приділено використанню штучного інтелекту, машинного навчання, великих даних (Big Data) та автоматизації маркетингових процесів. Описано основні технологічні тренди в побудові МІС, такі як інтеграція з CRM-та ERP-системами, використання цифрових інструментів персоналізації контенту, аналізу поведінки споживачів та реальної маркетингової аналітики. Запропоновано підходи до конструювання сучасних маркетингових інформаційних систем залежно від потреб підприємств, їх масштабу і призначення. Визначено перспективи розвитку МІС, зокрема, у контексті впровадження хмарних технологій, штучного інтелекту, інтернету речейта удосконалення механізмів управління даними.
Information-analytical support of marketing: modern trends and challenges
The article is devoted to the study of the essence, structure, properties, capabilities and prospects for the development of modern marketing information systems (MkIS). The relevance of this study is due to the rapid development of digital technologies and the growing need for their integration into the marketing activities of enterprises. The purpose of the article is to analyze modern approaches to the development of a system of information and analytical support for marketing activities, to determine its key components, functional capabilities and development prospects. Among the research methods, the main ones are: analysis of scientific literature, comparative analysis of marketing information systems, as well as generalization and systematization of data on the implementation of digital technologies in marketing analytics. The study found that marketing information systems have evolved from simple means of collecting and processing data to complex integrated platforms that include artificial intelligence, machine learning, big data analytics (Big Data) and automation of marketing processes. The main technological trends in the development of MkIS are identified, in particular, integration with CRM and ERP systems, the use of digital tools for content personalization, consumer behavior analysis and real-time marketing analytics. A key aspect of the development of MkIS is its effective integration into the general information system of the enterprise. Such integration provides synchronized data exchange between marketing, sales, finance, logistics and customer service, contributing to a unified approach to decision-making. The use of consolidated data streams allows enterprises to gain deeper insights into customers, increase operational efficiency and support data-driven strategic planning. In addition, the compatibility of MkIS with business intelligence (BI) tools and cloud solutions ensures its scalability and flexibility in response to changing market conditions. The practical value of the study lies in the formulation of recommendations for the development of modern marketing information systems adapted to the specific needs, scale and industry focus of enterprises. The identified prospects for the development of MkIS, in particular the use of cloud technologies, the Internet of Things, blockchain solutions, and the improvement of data management mechanisms, can be used by enterprises to optimize marketing analytics and increase the efficiency of business decision-making.
Keywords: інформаційна економіка; цифровізація; маркетингові інформаційні системи; Big Data; штучний інтелект; автоматизація маркетингу; персоналізація; information economy; digitalization; marketing information systems; Big Data; artificial intelligence; marketing automation; personalization